Faktor Penerimaan Pengguna Go-Pay Menggunakan Model UTAUT 2 - Hario Setyadi; Shabrina Shabrina; Putut Pamilih Widagdo (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
E-wallet is an example of a form of server-based finance technology which requires a smartphone and internet network to use. There are several e-wallet provider platforms in Indonesia, one of which is Go-pay. One of the determining factors for the success of a system is in terms of user acceptance. The purpose of this study is to find out what factors influence Go-pay user acceptance using the UTAUT 2 model and the addition of perceived security variables. Respondents in this study were Go-pay users in Samarinda City. Data processing was carried out using the SmartPLS application version 4.0.8. The results of the study show that the variables that affect acceptance of Go-pay users in Samarinda City are performance expectancy, perceived security, and habit. The gender moderation influences the facilitating conditions and habit on user acceptance, while the age moderation does not affect user acceptance. The results of this study are expected to be an evaluation material for service providers in order to improve the services provided.